A Fallibilist Social Methodology for Today's Institutional Problems - Wettersten, John (Cambridge Scholars Publisher, 2022)
This book identifies and explains far-ranging consequences for methodology as a consequence of the observation that all rationality is social, and highlights the need for methodological reforms in publications and interactions among colleagues and research programs.The idea that all rationality is social needs to be part and parcel of all social scientific theories, which means that their content must be changed. Sociology needs to study the impact of social rules, economics must revise assumptions about how individual rationality impacts financial developments, and cognitive psychology must i.